The Radio Virtual Machine: A Solution for SDR Portability and Platform Reconfigurability - Risset, Tanguy; Ben Abdallah, Riadh; Fraboulet, Antoine; Durand, Yves (HAL CCSD, 2009)
International audience In this study we have presented a software architecture based on the virtual machine concept for SDR implementation. A high level abstraction language for the specification of PHY layer configurations has been proposed. In order to validate our concept and prove its practicality we have implemented IEEE802.11a PHY transmit and receive functionalities on a software demonstrator based on the Lua VM. This experiment has shown that both programming and execution model